The Role of Social Service Office in the Implementation of National Health Insurance System for Recipients of Contribution Subsidy - Rukmini, Rukmini; Ristrini, Ristrini; Oktarina, Oktarina (Jurnal Penelitian Kesejahteraan Sosial, 2018)
This study is aimed to determine the role of Social Service Office in the implementation of National Health Insurance System (JKN) for recipients of contribution subsidy (PBI) including the aspects of membership determination, poverty criteria, verification, validation, and implementation obstacles. It was an observational study with cross sectional design, which was conducted in Blitar and Malang City in 2015. The data were collected by conducting in-depth interviews and focus group discussion with the authorities of Social Service Office, City Health Office and BPJS and also with secondary data on membership and policy documents investigation. Social Service Offices in Blitar city and Malang city have conducted the updating of the membership of central PBI based on the Integrated Data Base of Social Protection Program (PPLS) in 2011. Blitar Social Service Office had not completed the verification and validation processes for local PBI participants yet. In 2014 Malang Social Service Office only legalized the result of the verification activity. In 2015 Malang Health Office conducted the validation and the Social Service Office also participated in. The verification and validation process of central PBI was conducted by Social Service Office and by Sub-district Social Welfare workers, assisted by social worker community (in Blitar City) and the village team (in Malang City). The obstacles in conducting verification and validation for central PBI are the limited allocation of district budget (APBD) and the limited number of human resources in the Social Service Office to get the society poverty data. It is needed the extended role of the Social Services Office, that does not lay only on the verification and validation of the center PBI but also on that of local District PBI.